Evaluation of carbamazepine uptake and metabolization by Typha spp., a plant with potential use in phytotreatment - Dordio, Ana (2012)
Phytoremediation technologies such as constructed wetlands have shown higher efficiencies in removal of pharmaceuticals from wastewaters than conventional wastewater treatment processes, and plants seem to have an important role in the removal of some of those compounds. In this context, a study was conducted to assess tolerance, uptake, and metabolism of the epilepsy drug, carbamazepine, by the macrophyte Typha spp. This evaluation was conducted in hydroponic solutions with 0.5–2.0 mg/L of this pharmaceutical for a maximum period of 21 days. The removal of carbamazepine from nutrient solutions by the plants reached values of 82% of the initial contents. Furthermore, a metabolite (10,11-dihydro-10,11-epoxycarbamazepine) was detected in leaf tissues indicating carbamazepine translocation and metabolism inside plants. Activities of antioxidant enzymes catalase, superoxide dismutase, and guaiacol peroxidase generally increase (after some mild initial inhibition in the case of the latter enzyme) as result of the abiotic stress caused by the exposure to carbamazepine, but ultimately Typha seemed able to cope with its toxicity. The results obtained in this study suggest the ability of Typha spp., to actively participate in the removal of carbamazepine from water when used in phytotreatment systems.